2016
DOI: 10.1371/journal.pgen.1006048
|View full text |Cite
|
Sign up to set email alerts
|

The AP-2 Transcription Factor APTF-2 Is Required for Neuroblast and Epidermal Morphogenesis in Caenorhabditis elegans Embryogenesis

Abstract: The evolutionarily conserved family of AP-2 transcription factors (TF) regulates proliferation, differentiation, and apoptosis. Mutations in human AP-2 TF have been linked with bronchio-occular-facial syndrome and Char Syndrome, congenital birth defects characterized by craniofacial deformities and patent ductus arteriosus, respectively. How mutations in AP-2 TF cause the disease phenotypes is not well understood. Here, we characterize the aptf-2(qm27) allele in Caenorhabditis elegans, which carries a point mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…ALDH1A1 plays a role in the proliferation and differentiation of mammary progenitor cells in the normal breast; clonogenicity is decreased upon ALDH1A1 knockdown . TFAP2B is thought to stimulate cell proliferation and suppress terminal differentiation of specific cell types during embryonic development . Mutations in TFAP2B cause Char syndrome, a disorder characterized by defective heart, craniofacial and limb development .…”
Section: Discussionmentioning
confidence: 99%
“…ALDH1A1 plays a role in the proliferation and differentiation of mammary progenitor cells in the normal breast; clonogenicity is decreased upon ALDH1A1 knockdown . TFAP2B is thought to stimulate cell proliferation and suppress terminal differentiation of specific cell types during embryonic development . Mutations in TFAP2B cause Char syndrome, a disorder characterized by defective heart, craniofacial and limb development .…”
Section: Discussionmentioning
confidence: 99%
“…We found that aptf-2 RNAi reduced GLP-1::V5 expression in the distal end of the germline (Figure 4B-C). In addition, aptf-2 RNAi lowered PZ germ cell number, as did an aptf-2(qm27) mutant that harbors a point mutation in the APTF-2 DNA binding domain (Figure 4Dand S6)(Budirahardja et al, 2016). In contrast, RNAi knockdown of aptf-1 and aptf-3/4 caused non-significant changes to GLP-1::V5 expression and PZ germ cell number (Figure 4B-D and S6).…”
mentioning
confidence: 90%
“…Syndecans are a family of transmembrane proteoglycans that play important roles in metazoan development, regeneration, tissue repair and homeostasis (Afratis et al, 2017). Syndecans consist of conserved cytoplasmic and transmembrane domains and more divergent ectodomains that carry differentially sulfated glycosaminoglycan (GAG) chains (Choi et al, 2011). These GAG chains consist of heparan sulfate (HS) and chondroitin sulfate (CS) that can interact with ligands, extracellular matrix proteins, cytokines, growth factors and small molecules to coordinate signaling, cell adhesion and host defence mechanisms (Choi et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…One-third of patients with BOFS also exhibit renal system anomalies 1 . Transcription factor AP2-alpha ( TFAP2A , OMIM number: 107580) is known to be the gene responsible for the development of BOFS, and specific TFAP2A functions have been elucidated in the affected tissues of patients with BOFS 2 5 . In the current report, we describe a family that has multiple anomalies that are clinically consistent with the BOFS spectrum and present results from genetic analysis of the affected members.…”
mentioning
confidence: 99%